Effects of heat pump drying temperature and dietary fat on carrot β-carotene bioaccessibility - Xiaofei, Sun; Wenxue, Zhu; Xinling, Li; Jinling, Fan (International Journal of Agricultural and Biological Engineering, 2017)
Dehydration can significantly extend the shelf life of dried carrots and still retain nutrition of provitamin A carotenoids. In vitro digestion model was used in this study to assess the effect of drying temperatures of heat pump and dietary fat on the bioaccessibility of β-carotene in carrots. Also, low-speed centrifugation was employed to obtain β-carotene release rate in supernatant. Microfiltration was applied to obtain β-carotene micellar rate in micelle phase. These assays were used as indicators to assess the bioaccessibility of the β-carotene. Despite higher drying temperatures had a negative effect on the retention rate of β-carotene in carrots, it showed a positive impact on the micellar rate. In addition, dietary fat significantly increased the release rate and micellar rate of β-carotene for both fresh carrots and dried carrot products, with the highest release rate and micellar rate obtained when 10% dietary fat was added. Therefore, the heat pump drying process and dietary fat can significantly improve the bioaccessibility of β-carotene in carrots, which may increase the β-carotene bioavailability to human. Keywords: bioaccessibility, in vitro digestion, β-carotene, carrot, heat pump drying DOI: 10.25165/j.ijabe.20171004.2375 Citation: Sun X F, Zhu W X, Li X L, Fan J L. Effects of heat pump drying temperature and dietary fat on carrots’ β-carotene bioaccessibility. Int J Agric & Biol Eng, 2017; 10(4): 234–242.